Secretion of cochlin-tomoprotein (LCCL) in the middle ear following acute tympanic injury: implications for perilymph fistula diagnosis - Bae, Seong Hoon; Ikezono, Tetsuo; Park, Haeng Ran; Kim, Hyoyeol; Matsumura, Tomohiro; Saito, Shiho; Maeda, Yukihide; Matsuda, Han; Jung, Jinsei (Frontiers in Neurology, 2025)
IntroductionCochlin is the most abundant protein in the inner ear. The cleaved N-terminal domain of cochlin, known as LCCL and referred to as CTP (cochlin tomoprotein) in clinical biomarker usage, is a perilymph-specific protein and is widely used as a biomarker to detect perilymph leakage. However, little is known about the secretion or presence of LCCL in the middle ear, even though it can result in false positives when using LCCL as a biomarker for perilymph leakage.MethodsWe conducted translational research in humans and mice. A retrospective observational study was conducted on human patients who underwent multiple CTP tests after tympanostomy. In parallel, an experimental study on cochlin and its cleaved product, LCCL, was performed in mice.ResultsWe found the exceptionally elevated level of CTP within 10 days after tympanostomy in humans regardless of the presence of definite perilymph leakage. In addition, we identified LCCL in the middle ear after tympanostomy in mice. The concentration of LCCL peaked at three days post-tympanic injury. Importantly, the origin of LCCL in the middle ear lavage was not from the inner ear but is secreted from the middle ear space especially the annular ligament, suggesting it functions as an innate immune response in the middle ear.ConclusionTympanostomy for the CTP test results in a false positive when the sampling is delayed. While LCCL is a reliable biomarker for clinically detecting perilymph fistula, the timing of its application should be carefully considered to avoid false-positive results.